Distinctive Features of Sorting Volleyball Players and their Preparation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article discusses the work aimed at the development of volleyball sport, methods of selecting volleyball players in groups using regulatory tests and exercises, the acquisition of skills and abilities in the main forms of techniques and tactics of playing volleyball, as well as ways of their preparation.